A Study of the Learning Styles of Malaysian Students - Ruslin Amir; Zalizan Mohd Jelas (UiTM Publisher, 2011)
This study examines the learning style of students at Universiti Kebangsaan Malaysia. A translated version of the Grasha-Riechmann Learning Style Inventory was distributed to students in pure science, social science and professional courses. Results indicated that students from different fields of study varied very slightly but not significantly in their learning style. The male students showed a slightly higher inclination towards Independence and Avoidance learning styles while female students were found to be slightly more Participative and Competitive. It was found that Collaborative and Competitive learning styles were dominant among UKM students and that Collaborative, Dependent and Participative styles were associated with academic performance. The implications of these findings are discussed in terms of university teaching and learning to accommodate different learning style of students in order to meet the objectives and vision of the national university.